Spectrophotometric determination of reaction rates and kinetic parameters of a BAHD acyltransferase using DTNB (5, 5′-dithio-bis-[2-nitrobenzoic acid]). (April 2018) - Sullivan, Michael L.; Bonawitz, Nicholas D.
Graphical abstract: Highlights: DTNB is a reagent that can be used to quantify free coenzyme A (CoA). The reaction catalyzed by hydroxycinnamoyl-CoA acyltransferases (HCTs) releases CoA. Here we describe a method to measure HCT reaction rates in real time using DTNB. We report the kinetic parameters of a specific HCT determined with this method. The approach should be applicable to other BAHD family acyltransferases. Abstract: Hydroxycinnamoyl-Coenzyme A (CoA) hydroxycinnamoyl transferases are BAHD family acyltransferases that transfer hydroxycinnamoyl moieties from a CoA-thioester to an acceptor amine or alcohol to form an N -hydroxycinnamoyl amide or O -hydroxycinnamoyl ester, respectively, with the concomitant release of free CoA. One approach to measure reaction rates for these enzymes is to quantify the hydroxycinnamoyl amide or ester reaction product following chromatographic separation of reaction components. This approach can be labor-intensive and time-consuming. As an alternative, we examined the use of 5, 5′-dithio- bis -(2-nitrobenzoic acid) (DTNB, Ellman's reagent) to spectrophotometrically quantify, in real time, the release of free CoA during the transferase reaction. Using a hydroxycinnamoyl-CoA:l -DOPA hydroxycinnamoyl transferase as a model, we show that DTNB has little to no effect on the transferase reaction and can be used to provide a good estimate of hydroxycinnamoyl amide formation, thus allowing for the quick and easy collection of reaction rate data and determination of transferase kinetic parameters. This approach should be applicable to a wide range of hydroxycinnamoyl-CoA and other BAHD acyltransferases.